Recognizing the Fundamental Right to be Fat: A Weight-Inclusive Approach to Size Acceptance and Healing From Sizeism. Issue 1 (3rd April 2019) - Calogero, Rachel M.; Tylka, Tracy L.; Mensinger, Janell L.; Meadows, Angela; Daníelsdóttir, Sigrun
Abstract: Sizeism permeates and shapes how scientific and professional communities—including therapists—perceive, understand, and behave toward anyone considered fat. In this article, we use scientific evidence to argue for the recognition and establishment of fat acceptance to subvert sizeism. We first critically review the Weight Normative Approach, which dominates scientific discourse on weight, despite being based on sizeist assumptions that are discredited by data. We then articulate the tenets of the Weight Inclusive Approach, which honors size diversity and the promotion of wellness within a social justice framework. We end with strategies for therapists to align their practice with the Weight Inclusive Approach.